2001
DOI: 10.1042/bj3590621
|View full text |Cite
|
Sign up to set email alerts
|

Sulphatides trigger polymorphonuclear granulocyte spreading on collagen-coated surfaces and inhibit subsequent activation of 5-lipoxygenase

Abstract: Sulphatides are sulphate esters of galactocerebrosides that are present on the surfaces of many cell types and act as specific ligands to selectins. The present study was undertaken to investigate the effect of sulphatides on polymorphonuclear granulocyte (PMN) attachment, spreading and 5-lipoxygenase (5-LO) metabolism. Sulphatides, but not non-sulphated galactocerebrosides, dose-dependently enhanced attachment to collagen, as measured by the myeloperoxidase assay. Studies with blocking antibodies indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Subsequent observations have further indicated that nuclear import of 5-LO is a regulated process. Nuclear import can be triggered by adherence (2,4,11), by recruitment (2, 3), or by cytokines (5,12). Conditions that cause nuclear import of 5-LO can enhance (2,5,12) or suppress (4) LT production.…”
mentioning
confidence: 99%
“…Subsequent observations have further indicated that nuclear import of 5-LO is a regulated process. Nuclear import can be triggered by adherence (2,4,11), by recruitment (2, 3), or by cytokines (5,12). Conditions that cause nuclear import of 5-LO can enhance (2,5,12) or suppress (4) LT production.…”
mentioning
confidence: 99%
“…It is known that L-selectin cross-linking [12,21] and sulphatides [8] induce activation of L2 integrins. Do they signal in a similar way to PMN attachment onto a collagen-coated surface?…”
Section: Resultsmentioning
confidence: 99%
“…The role of sulphatides as L-selectin signalling molecules was demonstrated also by increasing cytosolic free calcium and enhancing expression of TNF and interleukin-8 genes in human neutrophils [7]. We have previously reported that sulphatides stimulated adhesion of human neutrophils to surfaces coated with collagen and ¢bronectin [8]. Since this may proceed through an activation for NF-UB we have now studied its activation in neutrophils and found it triggered by sulphatides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PMNLs were isolated from freshly drawn EDTA-anticoagulated donor blood by standard techniques, as previously described (Sud'ina et al, 2001). Leukocyte-rich plasma was prepared by sedimentation of RBCs with 3% dextran T-500 at room temperature.…”
Section: Human Neutrophil and Red Blood Cell (Rbc) Isolationmentioning
confidence: 99%